EDUKASI PENGELOLAAN BIAYA PRODUKSI UNTUK MENINGKATKAN NILAI PRODUK LOKAL DESA KANCINAA KABUPATEN BUTON - Nur Zarliani Uli; Dwi Agustyawati; Muh. Deswan; Sania Sania (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community service activity aims to enhance community understanding of production cost management as an effort to increase the economic value of local products in Kancinaa Village, Buton Regency. The method employed was participatory education through seminars and interactive discussions involving local business actors and community groups. The educational materials focused on introducing production cost components, simple cost calculation techniques, and their relationship with product innovation and downstream processing. The results indicate an improvement in participants’ understanding of production cost management, as reflected in their ability to determine more accurate and rational selling prices. Furthermore, participants were able to identify business opportunities based on local commodities, such as areca nut and coconut, which have the potential to be developed into value-added products. Overall, this activity contributes to strengthening community capacity in managing local enterprises and supports sustainable rural economic development.